Spatial Analysis of Slum Levels and Settlement Planning Based on Environmental Vulnerability in The Babakan Raya Area, Babakan Village, Dramaga District, Bogor Regency - Aubrey Naftali Sitorus; Sutoyo; Zainab Ramadhanis; Yuli Suharnoto; Andik Pribadi (Departemen Teknik Sipil dan Lingkungan IPB, 2026)
The redevelopment of the slum area in Community Unit CU (Rukun Warga/RW) 07 Babakan Raya, Dramaga District, is a strategic step to reduce slum conditions while improving the quality of the area's infrastructure. This study aims to identify and analyze the existing slum conditions based on basic infrastructure, land use, building density, and environmental quality, and to develop a spatial planning concept based on spatial analysis to produce an adaptive and sustainable site plan. The methods used include a physical survey in the field, involving 81 respondents through crowdsourcing, and a Weighted Overlay analysis based on the criteria outlined in the Regulation of the Minister of Public Works and Public Housing No. 14/PRT/M/2018. The results showed that 56% of respondents identified building quality as the main factor contributing to slum conditions, followed by drainage problems at 23%. The spatial analysis identified a severe slum area of 9.220 m² located in the southern part of CU 07, while the mild slum area reached 61.210 m². The projected population of Babakan Raya in 2044 is estimated to accommodate 6.500 people, with a density of approximately 573 people per hectare. As a technical response, a spatial plan for the development of the area was prepared in accordance with SNI 03-1733-2004 to improve building layout, drainage systems, and environmental quality in the future. Implementation of this plan is expected to create a healthier, safer, and more sustainable residential environment.